Granulomatous leptomeningitis in a goat associated with infection by Cryptococcus neoformans - Rosa, Fábio B.; Rubin, Mara I. B.; Olinda, Roberio G.; Leal, Paula V.; Lima, Stephanie C.; Pupin, Rayane C.; Gomes, Danilo C.; Lemos, Ricardo A. A.; Martins, Tessie B.; Rodrigues-Hoffmann, Aline; Barros, Claudio S. L. (Brazilian Journal of Veterinary Pathology, 2016)
A case of granulomatous leptomeningitis caused by Cryptococcus neoformans is described in a 2-year-old mixed-breed, female goat which presented acute neurological signs including ataxia, nystagmus, bilateral blindness, opisthotonus, hyperesthesia, and spastic paresis of forelimbs. Granulomatous inflammation was detected in the pia arachnoid covering the frontal, parietal and occipital lobes of the telencephalon; cerebellum, thalamus, mesencephalon, pons, medulla, and cervical and thoracolumbar segments of the spinal cord. Yeast-like organisms with morphology compatible with Cryptococcus spp. were observed. A 350 base pair sequence was amplified from DNA extracted from the formalin fixed paraffin embedded (FFPE) tissue. The amplified sequence matched 100% Cryptococcus neoformans. It is suggested that cryptococcal meningitis should be included in the differential diagnosis list of goat diseases with neurological signs such as ataxia, opisthotonus, nystagmus, hyperesthesia and spastic paresis.